(untitled) (Experimental biology, 2015)
Investigation of storage proteins electrophoretic spectra has been carried out for wheat somaclonal lines obtained from the long-term callus tissues. Mutations in gliadin and glutenin spectra have been revealed for somaclonal R4 line of cv. Otan with red coloured grain, in gliadin spectra – for R1, R2 lines of cv. Kazakhstanskaya 25 with antocian ear. Zero mutation in glutenin spectra has been found in R1, R2 lines of G4 hybrid (Cel.3C х Kaz.15).